Usurping Difference in the Feminine Fantastic from the Riverplate - María B. Clark (Studies in 20th & 21st Century Literature, 1996)
This study intended to define the concept of a feminine fantastic as a narrative mode in contemporary short fiction by women writers from Argentina and Uruguay. As a point of departure, the study examined the narrative techniques and conventions of the fantastic and their strategic use for the expression of feminine concerns. The concept of the feminine was used in the sense of referring to an interpretation of femininity as a construct of language rather than an essentially feminine narrative mode based on a biological gender division. An overview of fantastic short stories by women writers from Argentina and Uruguay examined the use of a gender-coded discourse and its subversion as the controlling strategy of the feminine fantastic. The study proposed that the feminine fantastic, because of its foregrounding of the inherent power relations of discourse and language, may also become a political practice for women writers. It was found that the subversion of reality in this narrative mode is often linked to the deconstruction of the binary oppositions underlying gender identity and difference, and that the strategic use of the fantastic may serve the deconstruction of cultural concepts that traditionally engender hierarchical and oppressive meanings in patriarchal discourse.
Keywords: Argentine literature; Uruguayan literature; feminine; feminine literature; feminine fantastic; narrative mode; femininity; language; gender; power; power relations; discourse; oppression; patriarchal discourse